Electrochemical research on corrosion behavior of A3 steel in compound sodium molybadate and organic inhibitor solution. Issue 1 (June 2015) - Sun, C X; Chen, Y M; Xu, H W; Zhang, M; Chen, M; Xue, M; Wu, J Y; Huang, C S
Abstract: The electrochemical corrosion behavior of A3 in compound sodium molybdate and organic inhibitor solution was tested by the electrochemical workstation method. The concentration of the compound inhibitor set to range 250 mg/L to 3000 mg/L. The polarization curve results of A3 in different concentration inhibitor solutions show that the inhibitor markedly represses the anodic processes. The EIS has two time constant. The extreme concentration is 1500 mg/L.